The Analysis of Technological Pedagogical Content Knowledge (TPACK) of Elementary Teachers in Using Augmented Reality as Learning Media - Nurmatin, Suci; Abdurrahman, Dudung; -, Holijah (Al-Aulad: Journal of Islamic Primary Education, 2024)
The rapid development of technology has an impact on the field of education. The use of technology in the field of education, one of which is an effort to increase the efficiency and effectiveness of the learning process. Elementary school teachers' understanding of technology is integrated with TPACK capabilities. TPACK skills are important for an elementary school teacher to have in the process of delivering learning. In conveying learning, media is needed, in this case the media used is technology-based learning media, namely augmented reality. This research aims to analyze the TPACK abilities of elementary school teachers in using technology-based learning media, namely augmented reality, as well as as a reference for carrying out further research related to developing augmented reality as a learning medium. The research was conducted qualitatively by involving ten elementary school teachers. Next, the ten teachers were used as research subjects who in this study are called participants. Data were collected using a questionnaire distributed to ten participants using Google Form and then analyzed using coding. The results of the research show that the TPACK abilities of ten artists have reached their maximum but their use in augmented reality is still very minimal. Thus, it can be concluded that TPACK's ability to use augmented reality as a learning medium for the ten participants is still very minimal and the next step is to develop augmented reality as a learning medium in elementary schools.